First Evidence: TRAP-Induced Platelet Aggregation Is Reduced in Patients Receiving Xabans. (September 2018) - Nehaj, Frantisek; Sokol, Juraj; Ivankova, Jela; Mokan, Michal; Kovar, Frantisek; Stasko, Jan; Mokan, Marian
The availability of direct oral anticoagulants has caused a paradigm shift in the management of thrombosis. Rivaroxaban and apixaban are 2 direct oral anticoagulants whose target specificity is activated factor X (FXa). However, it is still not fully understood if and how xabans impact platelet function. This observational study aimed to assess the in vitro platelet function in patients with atrial fibrillation receiving xabans. This was a single-center study quantifying platelet aggregation in 41 patients treated with apixaban or rivaroxaban by light transmission aggregometry. The thrombin receptor activating peptide (TRAP)-induced platelet aggregation was significantly lower 2 hours after taking rivaroxaban or apixaban compared to baseline value (56.15% [8.53%] vs 29.51% [12.9%]; P = .000). Moreover, concomitant use of angiotensin-converting enzyme blockers, proton pump inhibitors, and statins reduces the efficiency of xabans. The TRAP-induced platelet aggregation was reduced in patients with cardiovascular disease 2 hours after receiving xabans.